Effect of geometry on the mechanical properties of Ti-6Al-4V Gyroid structures fabricated via SLM: A numerical study. (15th December 2019) - Yang, Eric; Leary, Martin; Lozanovski, Bill; Downing, David; Mazur, Maciej; Sarker, Avik; Khorasani, AmirMahyar; Jones, Alistair; Maconachie, Tobias; Bateman, Stuart; Easton, Mark; Qian, Ma; et al.
Abstract: Triply Periodic Minimal Surface (TPMS) structures fabricated via Additive Manufacturing (AM) have recently emerged as being appropriate candidates for high-value engineered structures, including porous bio-implants and energy absorbing structures. Among the many TPMS designs, Gyroid structures have demonstrated merits in AM manufacturability, mechanical properties, and permeability in comparison to traditional lattice structures. Gyroid structures are mathematically formulated by geometric factors: surface thickness, sample size, number of surface periods, and the associated isovalue. These factors result in a continuous surface with a topology-specific structural response. Quantifying the effect of these factors on overall structural response requires substantial computational and experimental resources, and little systematic data exists in the literature. Using a numerical approach, cubic Gyroid structures of various designs were simulated under quasi-static compression, using a simulation model verified with experimental data for AM Ti-6Al-4V specimens fabricated by Selective Laser Melting (SLM). The influence of geometric factors on structural response was quantified with OFAT (One Factor At a Time) and Taguchi methods. The results identify the number of cells and surface thickness strongly influence both modulus and compressive strength. These findings were used to theoretically develop a Gyroid structure that imitates both elastic modulus and compressive strength of human cortical bone. Graphical abstract: Unlabelled Image Highlights: Surveyed SLM Ti-6Al-4V Gyroid structures under compression loading are shown to behave as bending-dominated structures. An SLM Ti-6Al-4V fabricated Gyroid shows distinct surface morphology between upward and downward facing surfaces. A numerical model of a Gyroid structure was constructed which showed excellent agreement with experimental results. Gyroid stiffness and strength increase with cell number and surface thickness and tend to reduce with isovalue and specimen size. A Gyroid structure was tuned to the stiffness of human cortical bone (∼16 GPa), for use in novel AM orthopaedic implants.